Price discovery of a speculative asset: Evidence from a Bitcoin exchange - Eric Ghysels; Giang H. Nguyen (Journal of Risk and Financial Management, 2019)
We examine price discovery and liquidity provision in the secondary market for bitcoin-an asset with a high level of speculative trading. Based on BTC-e's full limit order book over the 2013-2014 period, we find that order informativeness increases with order aggressiveness within the first 10 tiers, but that this pattern reverses in outer tiers. In a high volatility environment, aggressive orders seem to be more attractive to informed agents, but market liquidity migrates outward in response to the information asymmetry. We also find support to the Markovian learning assumption often made in theoretical models of limit order markets.
Keywords: 330; adverse selection; Bitcoin; cryptocurrency; learning; limit order book market; liquidity; price discovery; price impact